Analysis of the rearrangements associated with carcinogen-induced activation of the hamster thymidine kinase gene. - Barr, F G (1990)
We have previously shown that chemical carcinogen treatment of RJK92 hamster cells activates the quiescent thymidine kinase (TK) gene and that 20% of the TK+ variants have a rearrangement in the region 5' to the TK gene (Barr et al. (1986) Mol. Cell. Biol. 6, 3023-3033). After cloning the wild type 5' region to obtain detailed mapping data and hybridization probes, we localized the rearrangement breakpoints by Southern blot analysis to a 1.5 kb region 6 kb 5' to the origin of transcription. This analysis also demonstrated that the rearrangements consist at least partly of a deletion of wild type sequences 5' to this breakpoint region. The region near the transcription origin in the rearranged TK genes has a DNase I-sensitive chromatin conformation and a DNase I hypersensitive site as well as the previously described domain of demethylation (Ibid.). Though this domain of demethylation extends into the breakpoint region, the rearranged region is not associated with DNase I sensitivity nor hypersensitive sites. The rearrangement also does not detectably alter the growth-related regulation of TK activity in these cells.